A New Synthesis of l-Hydroxypipecolic Acid - Zhang, Zedong; Sun, Zhihua (Synlett, 2020)
A new synthetic approach toward l-hydroxypipecolic acid is described. This reaction sequence involves eight steps overall, starting from commercially available and inexpensive l-glyceraldehyde acetal. The strategy makes use of readily available reagents and can be used as a preparative synthesis of l-hydroxypipecolic acid. Most of the reaction steps proceed with moderate-to-good yields and do not require any unusual or expensive reagents.
Keywords: l-hydroxypipecolic acid; chiral piperidines; l-glyceraldehyde acetal; preparative synthesis; six-membered heterocycle